2022
DOI: 10.1109/tit.2022.3167554
|View full text |Cite
|
Sign up to set email alerts
|

Quadratically Constrained Myopic Adversarial Channels

Abstract: We study communication in the presence of a jamming adversary where quadratic power constraints are imposed on the transmitter and the jammer. The jamming signal is allowed to be a function of the codebook, and a noncausal but noisy observation of the transmitted codeword. For a certain range of the noise-to-signal ratios (NSRs) of the transmitter and the jammer, we are able to characterize the capacity of this channel under deterministic encoding or stochastic encoding, i.e., with no common randomness between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…‚ If we restrict ourselves to structured codes, e.g., nested lattice codes [11], then what list sizes are achievable? It was shown in [8] that O `1 δ log 1 δ ˘list sizes are achievable using random spherical codes. If we define S n´1 p0, ?…”
Section: A Overview Of Our Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…‚ If we restrict ourselves to structured codes, e.g., nested lattice codes [11], then what list sizes are achievable? It was shown in [8] that O `1 δ log 1 δ ˘list sizes are achievable using random spherical codes. If we define S n´1 p0, ?…”
Section: A Overview Of Our Resultsmentioning
confidence: 99%
“…For instance, Langberg [6] showed that if there exists a coding scheme that achieves a list size that is at most polynomial in the blocklength n, then even a small amount of shared secret key (just about Θplog nq bits kept secret from the adversary) between the sender-receiver pair suffices to ensure that the true message can be uniquely decoded by the receiver. List decoding can also serve as a useful proof technique for obtaining bounds on the capacities of other adversarial channels [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations